Valorisation of glucose into biofuels and high value-added chemicals using zeolites as catalysts. - Torres-Olea, Benjamín; Pérez-Merchán, Antonio Manuel; García-Sancho, Cristina; Cecilia-Buenestado, Juan Antonio; Moreno-Tost, Ramón; Maireles-Torres, Pedro Jesús (My University, 2023)
Hexose sugars can be valorised under acidic conditions to produce the platform chemical 5-hydroxymethylfurfural (HMF), which can be transformed in a broad spectrum of chemicals with applications as biofuels or monomers for polymers [1]. 5-ethoxymethylfurfural (EMF) is one of the derivatives of HMF useful as biofuel or fuel additive, produced usually from the etherification of HMF with ethanol. However, the high price of HMF is an important drawback for its use as feedstock for the production of EMF, which, together with the low yields and selectivity that are often attained by treating biomass or biomass derived compounds, are limiting its industrial application. In this work, several zeolites with different morphologies and chemical compositions have been employed as acid catalysts for the etherification reaction of HMF and ethanol to produce EMF, as well as the direct conversion of glucose into EMF.
Keywords: Glúcidos - Aplicaciones industriales; Catálisis heterogénea; 5-hidroximetilfurfural; 5-etoximetilfurfural; Deshidratación; Eterificación; Zeolitas